Between Work and Nonwork: Precarious Transitions through Life Stories and Everyday Life - Murgia, Annalisa (Narrative Works, 2012)
This paper analyzes critical transitions in work careers and the methodological implications with regard to the study of risk biographies. It analyzes contemporary work trajectories taking into account a variety of fields and spheres of life that are articulated in different ways, events, perceptions, and representations that inspire people’s action. From a methodological perspective, the paper concentrates on the development and implementation of methods for the narrative analysis of biographical transitions. The criteria used for the risk biographies analysis assume that the actor is a sense-maker who thoughtfully and retrospectively interprets the shifts and the events of his/her life, defining their coherence with his/her own principles. Moreover, a narrative approach enables both a longitudinal analysis of the biographical transitions in life stories and the analysis of everyday transitions among paid work, unpaid work, and private life.